Theaflavin as Potential Multi-Target Anti-Inflammatory Agent in Periodontitis: An in silico Approach - Ferry Sandra; Trijani Suwandi; Ricky Anggara Putranto; Maria Leny Raiyon; Albert Albert; Visi Endah Pratitis (The Indonesian Biomedical Journal, 2026)
BACKGROUND: Periodontitis is a chronic inflammatory disease characterized by progressive periodontal tissue destruction and dysregulated inflammatory responses. Current therapies mainly target bacterial infection but are often less effective in controlling inflammation. Tea (Camellia sinensis) contains bioactive polyphenols with antimicrobial and anti-inflammatory properties, making it a promising alternative therapeutic candidate. However, molecular interactions of tea-derived compounds with inflammation-related proteins through molecular docking remain unclear. This study evaluate the binding affinity and interaction profiles of tea-derived compounds with inflammation-related to periodontitis protein targets using molecular docking.METHODS: Ligand and protein structures were retrieved from public databases and prepared using standard optimization protocols. Toxicity and pharmacokinetic properties were predicted using ProTox-3.0 and SwissADME, respectively. Molecular docking was performed using CB-Dock 2.0 with AutoDock Vina, and ligand-protein interactions were analyzed using Discovery Studio.RESULTS: All tested compounds, including catechin, epigallocatechin gallate (EGCG), theaflavin, and thearubigin showed low predicted toxicity. Theaflavin showed the strongest binding affinity across multiple targets, particularly against IRAK-4 (−9.8 kcal/mol), TLR4 (−9.2 kcal/mol), and IKK-β (−9.5 kcal/mol), supported by stable hydrogen bonds and hydrophobic interactions.CONCLUSION: Among all compounds, theaflavin exhibit strong multi-target binding potential against key inflammatory proteins in periodontitis, followed by EGCG and thearubigin. These findings support their potential as alternative or adjunctive anti-inflammatory agents, although further in vitro and in vivo validation are required.KEYWORDS: periodontitis, tea polyphenols, theaflavin, molecular docking, inflammation, NF-κB pathway